Опыт вращательного бурения скважин с применением гидродинамического усилителя осевой нагрузки - Бессонов, Ю.Д.; Слипенький, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
In work results of industrial check of working capacity and performance of application of the hydrodynamic amplifier of thrust load (the patent of Ukraine №200003266505) are resulted at boring. Mechanical speed at sinking of borehole in formations soft and a mean fortress is augmented in 1,45-1,7 times. The device steadily works at boring of a water supply well by depth of 150m.